Factor Associated with Underweight among People with Tuberculosis - Wildana Widad Fitriyana; Dewi Puji Ayuningrum (Universitas Airlangga, 2021)
Background: The relationship between Tuberculosis (TB) and nutritional status is a significant one. Patients with TB who are underweight face a higher risk of death. Purpose: This research aims to analyze the factors related to the occurrence of being underweight among TB patients at the Public Health Center (PHC) in Perak Timur, Surabaya. Method: This was an analytical observational study and used a cross-sectional design. The sample for this research was 41 respondents, who were TB patients and were undergoing treatment at the PHC in Perak Timur, Surabaya. Data collection was done from March 2020 to June 2020. Primary data was collected by conducting interviews using a questionnaire. Data analysis was performed using a chi-square test. Results: The results indicated that, out of the 41 respondents, there were 21 respondents who were underweight (51.22%). Descriptively, underweight TB patients were more likely to be in the intensive phase of treatment (90%), have a low income (56.76%), have a low education status (65.38%), and be unemployed (59.38%), with PR=0.43 and 95%CI=0.76–9.38. The results of this research indicated a link between the treatment phase and TB patients being underweight (p=0.01; PR=2.33; 95% CI=1.43–3.79), the level of education attained by underweight TB patients (p=0.04; PR=0.41; 95% CI=0.17–0.99), and the income of underweight TB patients (p=0.04; PR=0.43; 95%CI=0.30–0.63). The results of this research indicated that there was a correlation between the work status and TB patients being underweight (p=0.07; PR=2.67; 95%CI=0.76–9.38). Conclusion: The treatment phase, education level and income are significantly related to TB patients being underweight.